Bioactive Sesqui- and Diterpenoids from the Argentine Liverwort Porella chilensis - Gilabert Valero, José Miguel (2011)
Four fusicoccane-type diterpenoids (1−4), including the new 1 and 2; four pinguisane-type sesquiterpenoids (5−8); and two aromadendrane-type sesquiterpenoids (9 and 10) were isolated from an Argentine collection of the endemic liverwort Porella chilensis. The biofilm formation of the human pathogen Pseudomonas aeruginosa was inhibited by compounds 3 (53 and 47%), 9 (45 and 41%), and 10 (48 and 37%) at 50 and 5 μg/mL, respectively. Compounds 3, 9, and 10 also produced a slight decrease in bacterial growth and interfere with the process of quorum sensing at the same doses.